Plant metabolites and functional foods in metastatic breast cancer: a supportive strategy for management - Jha, Pritya; Anjum, Varisha; AL.-Khafagi, Ahmed Adnan; Joshi, Sweta; Kadi, Ammar; Anjum, Areefa; Naquvi, Kamran Javed; Potoroko, Irina (Frontiers in Pharmacology, 2025)
Breast cancer (BC) remains one of the leading causes of cancer-related mortality worldwide, with metastatic and triple-negative breast cancer (TNBC) subtypes presenting particular therapeutic challenges. This review critically explores the potential supportive role of plant-derived bioactive compounds present in functional foods and nutraceuticals in modulating cancer-related biological pathways. Metabolites such as flavonoids, alkaloids, terpenoids, and polyphenols have demonstrated anti-inflammatory, antioxidant, and pro-apoptotic effects in preclinical in vitro and in vivo studies. Specific compounds such as epiberberine, crocin, evodiamine, and extracts from Halodule uninervis have shown promising effects in limiting cancer cell invasion, proliferation, and angiogenesis. Advances in delivery technologies, including nanoformulations, may further enhance their bioavailability and targeted action. However, these findings are predominantly based on preclinical data, and rigorous in vivo validation and clinical trials are required to assess their translational potential. This review outlines emerging research directions and discusses how plant-derived compounds may contribute to integrated, evidence-based strategies for cancer care, particularly as adjuncts to conventional therapies rather than standalone treatments.